Corruption and the management of public safety: the governance of technological systems - Bennett, Simon Ashley (Routledge advances in management and business studies, 2024)
Graft is a common and persistent social pathogen that afflicts the developed and developing world in equal measure. This book describes, through the medium of international case studies, how graft undermines public safety and how, following a near-miss, incident or accident, investigators can use actor-network theory (ANT) to ascertain to what degree and through what mechanisms graft contributed to the event. The book introduces the reader to graft through a variety of case studies and explains how graft works against the public interest. The relatable case studies include the 1989 Hillsborough football stadium disaster, 2007 Adam Air crash, 2015-ongoing Volkswagen diesel emissions scandal and 2020 Beirut ammonium nitrate explosion (Lebanon). It demonstrates the threat graft poses to public safety, economic success and corporate and national reputation. By the end of the book the reader will have an understanding of the nature and extent of the problem of graft, how graft undermines safety, confidence and reputation, and how ANT can be used to identify and quantify graft in respect of the governance of technological systems and to ascertain to what degree and through what mechanisms graft contributed to a near-miss, incident or accident. Primarily aimed at an academic audience, this book will offer insights to students, researchers and faculty within the fields of risk, crisis and disaster management, as well as corporate governance and safety. The accessible nature of the book will also appeal to safety practitioners, risk managers and accident investigators